2016
DOI: 10.1088/1612-2011/13/5/055202
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical rotation in the diamond nitrogen-vacancy center

Abstract: The interaction of two orthogonally polarized beams and a diamond nitrogen vacancy (NV) center sample is investigated. It is shown that applying a static magnetic field parallel to the propagation direction of the probe beam makes the diamond NV center sample a birefringent medium. Electromagnetically induced transparency (EIT) is attained under the assumption of specific parameters. Moreover, it is demonstrated that the magneto-optical rotation (MOR) can be manipulated by the control beam. Our results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Rotation of right and left CP probe beam has some interesting application in the field of spectroscopy, magnetometry, communication optics, sensors, atomic clocks, optical limitation, birefringence based optical filters, and quantum memory [6][7][8][9][10][11][12]. MOR was observed in different atomic media both, theoretically and experimentally [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Rotation of right and left CP probe beam has some interesting application in the field of spectroscopy, magnetometry, communication optics, sensors, atomic clocks, optical limitation, birefringence based optical filters, and quantum memory [6][7][8][9][10][11][12]. MOR was observed in different atomic media both, theoretically and experimentally [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This prominence is attributed to their enduring electronic spin decoherence time, a notable feature even at room temperature [30][31][32][33][34][35][36]. Recent years have witnessed a surge in research exploring the extensive properties and intriguing phenomena associated with NV centers, recognizing their potential pivotal roles in quantum information and computing [37][38][39][40][41][42][43][44][45]. Pioneering studies include the successful demonstration of coherent population trapping in a single NV center within a diamond under optical excitation, showcasing the feasibility of all-optical control over single spins in diamond [37].…”
Section: Introductionmentioning
confidence: 99%
“…Another captivating study involves the three-dimensional localization of a single NV center in nanodiamond using positiondependent standing-wave laser fields in an external magnetic field [43]. Mortezapour et al have also explored the phenomenon of magneto-optical rotation within diamond NV centers, contributing to an enhanced understanding of the potential applications and capabilities of these quantum entities [44]. This collective body of research signifies the evolving landscape of quantum exploration and applications in the context of NV centers in diamond nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of temperature of the atomic system on MOR has been studied in multiple three-level electromagnetically induced transparency subsystems and the maximum rotation angle have been reported 45 degrees at T = 65 °C 4 . The coherent control of optical polarization has been studied in GaAs quantum well nanostructures 5 , metamaterials 6 , single- and multilayer graphene 7 , mesogenic organic molecules 8 , diamond nitrogen vacancy centers 9 and cavity QED 10 . Moreover, several experimental studies have been reported in generation and control of the MOR 1115 .…”
Section: Introductionmentioning
confidence: 99%